2022
DOI: 10.3389/fphys.2022.965827
|View full text |Cite
|
Sign up to set email alerts
|

Can phase angle from bioelectrical impedance analysis associate with neuromuscular properties of the knee extensors?

Abstract: Maintenance and improvement of neuromuscular functions is crucial for everyone regardless of age. An easy way to assess neuromuscular properties without muscle contraction is useful especially for those who cannot perform strenuous muscular force production, such as older adults and patients with orthopedic or cognitive disorders. Bioelectrical impedance analysis (BIA) can assess body electrical properties e.g., phase angle (PhA) which is regarded as muscle quantity/quality index. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…The leg phase angle was significantly associated with the twitch contractile properties of the plantar flexors (Figure 1). This supports the findings of a previous study (Hirata et al, 2022b), which elucidated the correlations between the thigh phase angle and twitch contractile properties of the knee extensors. Phase angle is a function of inverse of resistance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The leg phase angle was significantly associated with the twitch contractile properties of the plantar flexors (Figure 1). This supports the findings of a previous study (Hirata et al, 2022b), which elucidated the correlations between the thigh phase angle and twitch contractile properties of the knee extensors. Phase angle is a function of inverse of resistance.…”
Section: Discussionsupporting
confidence: 92%
“…This implies that the assessment of muscle function using segmental phase angle is more detectable for plantar flexors than for knee extensors. Although a previous study (Hirata et al, 2022b) reported that the thigh phase angle did not correlate with rapid force generation or neuromuscular activity in knee extensors, these associations might be masked because of the relatively low percentage volume of knee extensors in the thigh compared with that of plantar flexors. Phase angle possibly relates to rapid force generation and neuromuscular activity because of the following reports: Yamada et al (2017) reported that the phase angle evaluated from the lower extremities correlated with maximal power during a counter-movement jump, which is a multi-joint-level explosive strength.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…BIA has evolved over the past years to become a practical method to provide reliable parameters of low muscle mass, which has been incorporated into the recent diagnostic criteria of sarcopenia [ 2 ]. As variables obtained from BIA are also found to be associated with muscle function, BIA has become a promising tool for skeletal muscle evaluation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%